Pendidikan dan Pertumbuhan Ekonomi Sebagai Transformasi Kesejahteraan - Syawaluddin Syawaluddin (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2020)
A good education system has a strategic role to contribute to creating prosperity and peace through human development who has advantages in the current era of globalization. As a principle requirement, it is the government's duty and responsibility to create a good and quality education process so that in the end superior human resources will grow. If we try to study and link education with the macroeconomic aspects of the nation, there will be no direct or pragmatic short-term relationship or contribution. However, if education is understood as a planned and systematic form of business, then this is where it can be linked. Humans with good education will give birth to attitudes, traits that are more constructive, innovative and advanced. Thus with the help of technology, humans will be able to create work processes or production activities that can run more effectively, efficiently and productively, so that all human needs can be met quickly and precisely, which in turn will result in a more vibrant market and increase human productivity. This can lead to the creation of more conducive economic conditions, marked by increasingly steady economic growth. This is where the long-term role of education in the chain of macroeconomic aspects of a country. Several research results that have been compiled have also succeeded in finding a correlation between education and economic growth with various perspectives and measurement indicators.